2021
DOI: 10.3897/mycokeys.81.67785
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and taxonomy of Catenularia and similar fungi with catenate conidia

Abstract: The genus Catenularia (Chaetosphaeriaceae) was reviewed, and its relationships with morphologically similar fungi were evaluated using molecular and morphological data. Eleven species are accepted, four of which have been verified with molecular DNA data. The correct epithet ‘cupulifera’ is proposed for the type species C. cupuliferacomb. nov. Four other combinations are proposed, namely C. catenulatacomb. nov., C. elsikiicomb. nov., C. minorcomb. nov. and C. novae-zelandiaecomb. nov.Catenularia is an uncommon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 73 publications
1
9
0
Order By: Relevance
“…Chaetosphaeria was resolved as a polyphyletic genus in Chaetosphaeriaceae ( Figure 1 ), consistent with many previous studies [ 6 , 9 , 10 , 13 , 14 , 15 , 29 , 51 , 52 ]. The new species, Chaetosphaeria obovoidea , and three other Chaetosphaeria species are clustered in the subclade of Chaetosphaeria III.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Chaetosphaeria was resolved as a polyphyletic genus in Chaetosphaeriaceae ( Figure 1 ), consistent with many previous studies [ 6 , 9 , 10 , 13 , 14 , 15 , 29 , 51 , 52 ]. The new species, Chaetosphaeria obovoidea , and three other Chaetosphaeria species are clustered in the subclade of Chaetosphaeria III.…”
Section: Resultssupporting
confidence: 90%
“…Réblová et al [ 13 , 14 ] introduced six new genera namely Arcuatospora , Achrochaeta , Ericiosphaeria , Flectospora , Phialoturbella and Tubulicolla . The lineages of “ C atenularia ”-like taxa were recognized as a genus Fuscocatenula by Réblová et al [ 15 ]. Five lineages, Codinaeella , Nimesporella , Stilbochaeta , Tainosphaeriella and Xyladelphia , were proposed for “ Codinaea ”-like fungi by Réblová et al [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strains, their sources, and the GenBank accession numbers of sequences of ITS, 28S and tef1-α determined in this study are listed in Table 1. Accession numbers for sequences retrieved from GenBank and published in other studies [12,15,[28][29][30][47][48][49][50][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86] are listed in Table 1 and the Supplementary File: Table S1.…”
Section: Gene Markers Alignments and Phylogenetic Analysesmentioning
confidence: 99%
“…catenulata, Arecophila sp. and Diporotheca (Supplementary Tables 2, 3), suggests a temperate to tropical environment with freshwater habitats (Umali et al, 1999;Hawksworth and Lücking, 2017;Réblova et al, 2021). Previous paleobotanical and paleoecological studies indicated similar paleoenvironments for the lower Miocene of Na Hong with warm-temperate forest and Taxodium swamp with fern-sedge communities (Songtham et al, 2005;Sepulchre et al, 2010).…”
Section: Paleoenvironments Of Thailand and Slovakia Based On Fungal Compositionmentioning
confidence: 89%